Report on National Workshop - Ali, A M M Mostafa; Rahman, Md. Mostafizur; Saha, Champa Rani; Rahman, Syed Arman Akib; Haque, Md. Ehsanul; Nisha, Nusrath Jahan; Chitra, Naima Noshin; Ahmad, Salahuddin (CGIAR Initiative on Asian Mega-Deltas, 2024)
Due to low-lying and flat topography in the coastal region, Bangladesh is one of the top 10 nations that are mostly vulnerable to climate change and is subjected to riverine flooding (due to sea level rise), frequent cyclones, storm surge, heavy rainfall, tornados, river bank erosion, salinity, high population density, high level of poverty, and solely reliance of livelihoods on climate-sensitive sectors. Thus, climate change addresses a new depressing effect on coastal agriculture since agriculture in Bangladesh is highly sensitive to climate variability as crops require sustained ambient temperature for their growth, and abrupt heat or cold waves hamper productivity. However, to ameliorate such predicaments, the adoption of climate-smart agricultural practices and technologies is needed to ensure participatory planning and development. Adaptation planning is crucial to ensure the overall productivity of agriculture against climate change events. This project is an initiative to collect data and generate information for adaptation planning in the coastal region of Bangladesh.